A study of the Millennium Library Management System's effectiveness in the case of the De La Salle University Library - Jacob, Madelienn A.; Carcellar, Marie Desiree R. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Libraries and their parent institutions invest a large amount of money on the library software used by them. With the continuous change in the technological environment, how can libraries cope in order to meet the needs of every library user and to enhance the interaction between the library and its users? The De La Salle University Library resolved this problem by changing their library system from T-series to Millennium Library System.
This study is an investigation on the reasons of the institution in shifting from one library system to another and the success of their new library system. The respondents stated their attitude towards the new library system of their institution. The institution, itself, also has a positive attitude towards the new system and has allocated financial resources to acquire the new library system for their library. They have provided funds to acquire other peripherals they need for a successful implementation of the Millennium on their institution.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: De La Salle University; Integrated library systems